PEMBUATAN BIOGAS DARI BERBAGAI LIMBAH CAIR PABRIK KELAPA SAWIT - Irvan, Irma Suraya, Hari Tiarasti, Bambang Trisakti, Rosdanelli Hasibuan, Yoshimasa Tomiuchi (Jurnal Teknik Kimia USU, 2012)
The purpose of this research is to determine the effect of Fe level as trace metal on the quantity of biogas produced from the fermentation of palm oil mill effluent (POME). Materials used in this study included POME from one of the palm oil factories belong to PTPN IV, hydrochloric acid, sodium bicarbonate, and trace metal. Observed variables were volume of biogas, concentration of Fe in fermentor, rate of degradation total solid (TS) and volatile solid (VS), and CO2 at Hydraulic Retention Time (HRT) 6 days. Before HRT of 6 days reached, initial trace metal composition of Fe added were 25.2 mg / L, Co 0.42 mg / L and Ni 0.49 mg/ L. After that, composition of trace metal were consisted only Co and Ni. The results of this study showed that Fe as a trace metal did not affect the production or quantity of biogas and concentration Fe on level > 330 mg/L decreased the value of CH4, total solid (TS) and  volatil solid (VS). Thus, Fe in the trace metal is no longer required if there is a high content of Fe in POME because it can be toxic for microorganism in the fermentation of biogas.Keywords : biogas, concentration of Fe, fermentation of POME, trace metal, TS, VS.